Wari, a Karawitan Composition | Wari, Sebuah Komposisi Karawitan - I made Wira putra; Wardizal - (GHURNITA: Jurnal Seni Karawitan, 2023)
This creative musical composition work entitled "Wari" is a new composition work or a creative musical composition that offers new ideas, is contemporary, and prioritizes originality. The stylist imagines by systematically arranging a composition whose source of inspiration comes from the similarities in various types of ornamentation found in the ubitangangsa pemade, gangsa kantilan, reong instruments with other instruments. The stylist wants this creation to give a new impression and atmosphere, so to make this happen, the stylist wants to pack some melodic strands and ubit-ubitan or kotekan strands. All of that is packed with a base from something simple to something new. Here lies the novelty to the maximum extent of the stylist's ability to package creative works into something new. In this compositional work "Wari" the structure uses part such as part I,part II dan part III, but in this creative percussion musical composition, there is also a gagenderan and bapang part in the composition of gamelan percussion. average or the same from the processed form/garap motif of the instrument gangsa pemade, gangsa kantilanwhich is made kotekan or ubit-ubitan, while melodies such as penyacah, jublag, and jegogare also made up of melodies with the same portion as on the instruments of gangsa peme,gangsa kantilan. As well as processing musical elements such as dynamics (aes-uncab) and tempo.